BRCA1-Associated Protein Is a Potential Prognostic Biomarker and Is Correlated With Immune Infiltration in Liver Hepatocellular Carcinoma: A Pan-Cancer Analysis - Ju, Qiang; Li, Xin-mei; Zhang, Heng; Zhao, Yan-jie (Frontiers in Molecular Biosciences, 2020)
Background: BRCA1 associated protein (BRAP), is a critical gene that regulates inflammation related signaling pathway and affects patients’ prognosis in esophageal squamous cell carcinoma (ESCC). However, its roles in different cancers remain largely unknown. Methods: BRAP expression in human pan-cancer were analyzed via genotype-tissue expression (GTEx) and the cancer genome atlas (TCGA) database. Pearson correlation test were used to analyze the association between BRAP expression with mismatch repair (MMR) gene mutation and DNA methyltransferase. We evaluated the influence of BRAP on clinical prognosis by univariate survival analysis. Moreover, the correlation between BRAP and tumor immune infiltrates were analyzed using tumor immune evaluation resource (TIMER) database. Pearson correlation analysis was used to investigate the correlation between BRAP expression and immune checkpoint genes expression. Results: BRAP is abnormally overexpressed and significantly correlated with MMR gene mutation and DNA methyltransferase in human pan-cancer. Univariate survival analysis showed BRAP was significantly with patients’ overall survival (OS) in 6 cancer types, disease-free interval (DFI) in 3 cancer types, progression-free interval (PFI) in 2 cancer types. Remarkably, increased BRAP expression was strongly correlated with patients’ poor prognosis in liver hepatocellular carcinoma (LIHC), whether OS (P<0.0001, HR=1.1), DFI (P=0.00099, HR=1.06) or PFI (P=0.00025, HR=1.07). Moreover, BRAP expression was positively correlated with immune infiltrating cells including B cell, CD4+ T cell, CD8+ T cell, dendritic cell, macrophage cell, neutrophil cell in colon adenocarcinoma (COAD), kidney renal clear cell carcinoma (KIRC) and LIHC. BRAP expression showed strong correlations with immune checkpoint genes in LIHC. Conclusion: BRAP expression is increased in human pan-cancer samples compared with normal tissues. Overexpression of BRAP is correlated with poor prognosis and immune infiltrates in multiple cancers, especially in LIHC. These finding suggest BRAP can be used as a molecular biomarker for determining prognosis and immune infiltration in LIHC.